Safety analysis for vehicle guidance systems with dynamic fault trees. (June 2019) - Ghadhab, Majdi; Junges, Sebastian; Katoen, Joost-Pieter; Kuntz, Matthias; Volk, Matthias
Highlights: DFTs for a variety of safety concepts and E/E-architectures for autonomous driving. Systematic automated construction of DFTs for these concepts and architectures. Obtained the largest, industrially-relevant DFTs so far. Scalable analysis of DFTs allows automated evaluation of hardware partitioning. Abstract: This paper considers the design-phase safety analysis of vehicle guidance systems. The proposed approach constructs dynamic fault trees (DFTs) to model a variety of safety concepts and E/E architectures for drive automation. The fault trees can be used to evaluate various quantitative measures by means of model checking. The approach is accompanied by a large-scale evaluation: The resulting DFTs with up to 300 elements constitute larger-than-before DFTs, yet the concepts and architectures can be evaluated in a matter of minutes.